Modelling Supply Chain Coordination: An Application of Analytic Hierarchy Process under Fuzzy Environment - Rajendra Kumar Shukla; Dixit Garg; Ashish Agarwal (International Journal of Supply Chain Management, 2013)
Coordination of supply chain of trading partner plays a crucial role in improving overall supply chain performance. For allocating the component or services to trading partner, it would be significant to analyze the supply chain coordination of the trading partner. In order to prioritize supply chain coordination mechanisms the conventional methods are hardly adequate to deal with the imprecise or vague nature of linguistic assessment. To overcome this difficulty, fuzzy multi-criteria decision-making model is proposed. In this study, a fuzzy Analytic Hierarchy Process is applied for prioritization of coordination mechanisms for selected supply chain. A case study of Indian automotive parts manufacturing company is described to illustrate the application of the used method. This paper presents how Fuzzy Analytic Hierarchy Process (FAHP) can be applied to allow for evaluation and prioritization of mechanisms used to coordinate a supply chain. After determining, the coordination criteria that affect the Supply chain partner prioritization, fuzzy AHP method is applied to the problem and results related to the prioritization of coordination mechanisms are presented.